Leading Teacher Collaboration in Elementary School Through School Leader Adaptive Skills: A PLS-SEM Approach - Sumiati, Sumiati; Komariah, Aan; Kurniady, Dedy Achmad; Suryana, Asep (JETL (Journal of Education, Teaching and Learning), 2024)
The purpose of this study was to examine the relationship between school leader’s adaptive leadership skills and teacher collaboration in schools and explore the implementation of adaptive leadership skills determine on teacher collaboration. The study was conducted using a cross-sectional survey with a sample of 384 teachers in elementary school teachers from 65 public elementary schools in Bogor district West Java Indonesia. The data were collected through Adaptive Leadership Skills scale and the Teacher collaboration Survey. Structural Equation Modeling (SEM) with partial least square was used to estimate relationships among the variables. The study findings indicate that adaptive leadership skills (emotional intelligence, organizational culture, character, and development) were significantly and positively related to teacher collaboration in schools. The findings are discussed according to the related literatures.